Tackling air pollution in the Philippines - Tantengco, Ourlad Alzeus G; Guinto, Renzo R * (Elsevier, 2022)
Veronica Southerland and colleagues1 reported that between the years 2000 and 2019, most of the world’s urban population lived in areas with unhealthy concentrations of fine particulate matter (PM2·5). The global average urban PM2·5 concentration in 2019 was 35 μg/m³, which is seven times the 5 μg/m³ limit set by WHO in its 2021 guidelines, resulting in more than 1·8 million deaths in 2019.1 Among the world’s regions, the Western Pacific, where our country Philippines is located, is experiencing the highest levels of PM 2·5-attributable mortality, exceeding the global urban average. Indeed, the Philippines is not exempt from the enormous health burden of air pollution.